Vectorial competence of Glossina brevipalpis in the transmission of Trypanosoma congolense in the Matutuíne District, Maputo Province, Mozambique - Neves, Luís C.B.G (University of Pretoria, 2025)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2024.